TANGGUNG JAWAB PEMERINTAH DAERAH DALAM PEMBERIAN BANTUAN HUKUM BAGI MASYARAKAT MISKIN - Andros Timon (Jurnal Ilmu Pemerintahan Suara Khatulistiwa, 2021)
The purpose of this study was to determine how the responsibility of the local government in providing legal aid to the poor. The problem approach method that the author uses is a normative juridical approach, namely the way of collecting data sourced from legal library materials. The results of the study can be concluded that the provision of legal aid has great benefits for the development of education, awareness of the rights of the poor, especially economically, in access to justice, as well as social change in society towards improving the welfare of life in all areas of life-based on social justice for all. people of Indonesia. Lack of public knowledge about the law is one of the causes of the importance of providing assistance to people who are dealing with the law. The Regional Government may allocate the budget for the implementation of Legal Aid in the Regional Revenue and Expenditure Budget which is regulated by Regional Regulation. The budget allocation for the implementation of Legal Aid in the regions is adjusted to the financial capacity of the regions and based on the conditions of the people in the regions both culturally and culturally so that the Regional Regulations that are stipulated can be implemented and fulfill the sense of justice and the needs of the community. With the existence of a Regional Regulation that regulates the Implementation of Legal Aid, the constitutional rights of poor people or groups of people in the region can be guaranteed.